The Effectiveness of the Implementation of Food Independent Area Program in Ogan Ilir Regency - Komala Sari; Ahmad Febriyansyah (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2021)
Food Independent Area Program (KMP) was aimed for people in food insecure/needy area with the main purpose was to fulfill the family food needs and at the end, can increase the community income so that they can be more independent. The aims of this research were to find out how the implementation, participation and how much the contribution of the income from food independent area program to the family income. To answer how the implementation of food independent area program and participation of affinity group members to the food independent area program used descriptive analysis with likert scale. Meanwhile to find out the contribution of income from food independent area program to the family income used income anyalisis. This research concluded that the implementation of KMP program in South Pemulutan Sub-Dictrict Ogan Ilir Regency has only reached the fourth stage of the set five stages in food independent area, the average of community participation was 41,37 which mean the community pasticipation to the food independent area program at affinity village had high category or highly participating and an increase in the family income at food independent area of 31,36% or 5.799.000,00 Rupiah per year, from total income of 18.314.224,52 Rupiah per year.